2020
DOI: 10.1021/acsami.0c07979
|View full text |Cite
|
Sign up to set email alerts
|

Implications from Broadband Microwave Absorption of Metal-Modified SiC Fiber Mats

Abstract: Understanding the physical requirements for a broad bandwidth is vital for the design of high-efficiency microwave absorber. Our recent works on silicon carbide (SiC) fiber mats-based absorbers imply that metal modification (e.g., Fe or Hf) could benefit their bandwidth effectively. For verification, we fabricated a Co/SiC fiber mat via a similar electrospinning process and subsequent pyrolysis at 1400 °C in Ar atmosphere. The results indicate that after Co modification, the SiC fiber mats show elevated permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…So far, graphene [ 10 ], MoS 2 [ 11 ], CNT [ 12 ], SiC [ 13 ], and MXene have been recognized as representative candidate materials for high-efficiency EM absorbers. The two-dimensional structure of MXene is considered to be the most potential absorbing material due to its strong conduction loss and polarization loss provided by excellent conductivity and abundant surface groups (-OH, -O, -F) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, graphene [ 10 ], MoS 2 [ 11 ], CNT [ 12 ], SiC [ 13 ], and MXene have been recognized as representative candidate materials for high-efficiency EM absorbers. The two-dimensional structure of MXene is considered to be the most potential absorbing material due to its strong conduction loss and polarization loss provided by excellent conductivity and abundant surface groups (-OH, -O, -F) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer conversion is a method for preparing high temperature resistant FCFs from polymers containing silicon (Si), carbon (C), nitrogen (N) and other elements [133]. The polymer precursors are first processed into fibrous materials by fiber processing methods, such as electrospinning, solution Polymer conversion method is often used to prepare non-oxide ceramic fiber materials, and SiC fiber is the most studied [72,73,76,[134][135][136][137][138][139][140]. Hou et al [134][135][136][137]139] developed SiC fibers and a series of modified SiC fibers by electrospinning combined with polymer precursor conversion: First, the spinning solutions containing polymers, ceramic precursors and other ingredients such as modifiers are prepared, then the composite fibers are prepared by electrospinning process, and eventually the SiC fibers or modified SiC fibers are obtained by thermal curing and pyrolysis (Fig.…”
Section: Polymer Conversionmentioning
confidence: 99%
“…[132]. Copyright 2020, American Chemical Society Currently, iron (Fe) [139], Fe 3 Si [135], Fe 3 O 4 [154], hafnium carbide (HfC) [137], cobalt (Co) [134] have been reported as modifiers of SiC fibers. Taking HfC as an example, the addition of a small amount of HfC component in the SiC fibers can significantly improve the electrical conductivity of the fibers, thus improving the dielectric property and electromagnetic wave absorption property (Fig.…”
Section: Electromagnetic Wave Absorptionmentioning
confidence: 99%
“…An excellent precursor of adjuvant should simultaneously have good stability, well solubility, and excellent spinnability, and the adjuvant had a synergistic effect for losing EM wave energy. [21][22][23] For instance, Hou et al reported a range of modified SiC/C fibers by adding metal acetylacetone complex (M(AA), M = Fe, Zr, Hf, or Co) to enhance their conductivity and EM wave absorption performance. [22][23][24][25] After researching a large number of pieces of literature, we choose the molybdenum acetyl acetone (MoO 2 (acac) 2 ) as adjuvant, due to the excellent spinnability and good solubility.…”
mentioning
confidence: 99%
“…[21][22][23] For instance, Hou et al reported a range of modified SiC/C fibers by adding metal acetylacetone complex (M(AA), M = Fe, Zr, Hf, or Co) to enhance their conductivity and EM wave absorption performance. [22][23][24][25] After researching a large number of pieces of literature, we choose the molybdenum acetyl acetone (MoO 2 (acac) 2 ) as adjuvant, due to the excellent spinnability and good solubility. [26] What's more,…”
mentioning
confidence: 99%